Local employees working in a terrorist region: HR managers' perceptions. (2nd October 2018) - Junaid, Fatima Ali; Haar, Jarrod; Parker, Jane
ABSTRACT: This study explores the influence of living under ongoing terrorism on employee behaviours. We argue that the context of living under ongoing terrorism, and its influence on local employees is an area which needs further exploration. Set in Pakistan, one of the five worst terrorism-affected countries in the world, we draw on semi-structured interviews to explore the nature of these stressors and their effects on local employee behaviours. Fifteen managers reflected on their workplaces and thematic analysis surfaced three major themes: (1) terrorism stressors, (2) job stressors and (3) employee behaviours. Terrorism stressors were identified using the sub-themes of loss, fear, trauma, risk to life and resilience/habituation. Job stressors reflected factors similar to western research such as workload and time pressures. We find that the stressors often overlap and might interplay with each other. Our final theme relates to how terrorism stressors affect employee behaviours, where three sub-themes emerged, including performance, absenteeism, turnover and voluntary behaviours. These behaviours were both positive and negative. We contribute to the HRM literature by probing an important context for working amidst terrorism and how terrorism and job stressors can affect local employees. Our findings indicate that employees still perform and behave humanely under extreme conditions; implications of the study for organisations and research are discussed.